2010
DOI: 10.1038/emboj.2010.280
|View full text |Cite
|
Sign up to set email alerts
|

The tumour suppressor C/EBPδ inhibits FBXW7 expression and promotes mammary tumour metastasis

Abstract: Inflammation and hypoxia are known to promote the metastatic progression of tumours. The CCAAT/enhancerbinding protein-d (C/EBPd, CEBPD) is an inflammatory response gene and candidate tumour suppressor, but its physiological role in tumourigenesis in vivo is unknown. Here, we demonstrate a tumour suppressor function of C/EBPd using transgenic mice overexpressing the Neu/Her2/ERBB2 proto-oncogene in the mammary gland. Unexpectedly, this study also revealed that C/EBPd is necessary for efficient tumour metastasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
153
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(164 citation statements)
references
References 69 publications
10
153
1
Order By: Relevance
“…Most previous studies have focused on the tumor-suppressive role of FBXW7 in tumor cells themselves. The putative tumor suppressor C/EBPδ was shown to inhibit FBXW7 expression and to promote mammary tumor metastasis through attenuation of FBXW7-dependent degradation of mTOR in tumor cells (52). We have now discovered what we believe to be a new aspect of FBXW7 function in tumor suppression -namely, its role in the host environment to suppress cancer metastasis.…”
Section: Discussionmentioning
confidence: 82%
“…Most previous studies have focused on the tumor-suppressive role of FBXW7 in tumor cells themselves. The putative tumor suppressor C/EBPδ was shown to inhibit FBXW7 expression and to promote mammary tumor metastasis through attenuation of FBXW7-dependent degradation of mTOR in tumor cells (52). We have now discovered what we believe to be a new aspect of FBXW7 function in tumor suppression -namely, its role in the host environment to suppress cancer metastasis.…”
Section: Discussionmentioning
confidence: 82%
“…Increased CEBPD participates in the transcription of peroxisome proliferator-activated nuclear receptor g 2 (PPARG2), an adipogenic and proapoptotic inducer, and DNA-damage-inducible protein 153 (GADD153, also known as CHOP), a proapoptotic inducer (13,14). A recent study demonstrated that loss of CEBPD might contribute to the initiation of breast cancer (15). Moreover, inactivated CEBPD was observed in HCC and cervical cancer via an epigenetic effect (16).…”
Section: Introductionmentioning
confidence: 99%
“…F-box/WD repeat-containing protein 7 (Fbxw-7), is a tumor suppressor that has been demonstrated to regulate several oncoproteins (10) including, cyclin D, cyclin E (11-13), c-Myc (14,15), aurora kinase A (16), Notch (17)(18)(19)(20) and the proto-oncogene c-Jun (21,22) c-Jun, an extensively-studied member of the JUN family, has been associated with cell proliferation, tumor cell survival and apoptosis (23). Therefore, it is important to investigate the Fbxw-7-associated signaling pathways involved in the proliferation of breast cancer.…”
Section: Introductionmentioning
confidence: 99%